Complexity of rule sets in mining incomplete data using characteristic sets and generalized maximal consistent blocks. (18th September 2020) - Clark, Patrick G; Gao, Cheng; Grzymala-Busse, Jerzy W; Mroczek, Teresa; Niemiec, Rafal
Abstract: In this paper, missing attribute values in incomplete data sets have three possible interpretations: lost values, attribute-concept values and 'do not care' conditions. For rule induction, we use characteristic sets and generalized maximal consistent blocks. Therefore, we apply six different approaches for data mining. As follows from our previous experiments, where we used an error rate evaluated by ten-fold cross validation as the main criterion of quality, no approach is universally the best. Thus, we decided to compare our six approaches using complexity of rule sets induced from incomplete data sets. We show that the smallest rule sets are induced from incomplete data sets with attribute-concept values, while the most complicated rule sets are induced from data sets with lost values. The choice between interpretations of missing attribute values is more important than the choice between characteristic sets and generalized maximal consistent blocks.